Pollution Load Allocation on Water Pollution Control in the Citarum River - Mitta Ratna Djuwita; Djoko M. Hartono; Setyo S. Mursidik; Tri Edhi Budhi Soesilo (Journal of Engineering and Technological Sciences, 2021)
The Citarum River is a strategic river in Indonesia, but has poor water quality.  The existing pollution control program has no impact on the river's water quality, because it uses a regulatory approach and prioritizes industrial sources. To improve the quality of the river, every pollutant source needs to reduce the pollution load discharged into the river based on the ability of the river to receive pollution. The purpose of this study was to measure pollution load allocation based on the total maximum daily load (TMDL) of the river. The results show that non-point sources contribute the highest pollution load (85%) compared with point sources (15%). The results of the measurement of pollution load allocation showed that the highest contribution of pollution load was from domestic waste (83.5%), followed by industrial waste (6.6%). The target of pollution load reduction for domestic sources is 81.8%, and for industries is 79.5%. The improvement of river water quality should be started at tributaries and domestic sources. This study can be used by local governments to develop water pollution control programs, for instance as a basis for determining the wastewater discharge permit of pollutant sources and permit trading.